2011
DOI: 10.1007/s11920-010-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Anxiety Disorders in Children and Adolescents

Abstract: This article reviews the current screening and assessment tools for anxiety disorders in children and adolescents, as well as evidence-based treatment interventions for these disorders. The following anxiety disorders are discussed: separation anxiety disorder, generalized anxiety disorder, specific phobia, panic disorder, social anxiety disorder (social phobia), and selective mutism. There are several well-studied screening and assessment tools to identify childhood anxiety disorders early and differentiate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 84 publications
1
29
0
1
Order By: Relevance
“…In the studies examined in this chapter, the most common adverse events (AEs) were gastrointestinal symptoms, namely, abdominal discomfort and nausea. Other common, usually mild and transient, side effects of SSRIs include headaches, motor restlessness, and insomnia (Connolly et al 2011 ). Less common AEs are disinhibition and behavioral activation.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…In the studies examined in this chapter, the most common adverse events (AEs) were gastrointestinal symptoms, namely, abdominal discomfort and nausea. Other common, usually mild and transient, side effects of SSRIs include headaches, motor restlessness, and insomnia (Connolly et al 2011 ). Less common AEs are disinhibition and behavioral activation.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…160 Besides the SSRIs and venlafaxine, three studies about the use of imipramine among patients with anxiety disorders have demonstrated its effectiveness in non-OCD disorders. 161 However, TADs are considered secondary choices due to their less favorable adverse effects and the fact that they require continuous monitoring of blood and cardiac irregularities. 158 There is no evidence supporting the use of benzodiazepines in the treatment of pediatric anxiety disorders.…”
Section: Figurementioning
confidence: 99%
“…One needs to focus on the onset and development of anxiety symptoms, the severity of symptoms, effects of symptoms on functioning, and stressors related to symptoms during the interview [5]. Although the most commonly used method for evaluation is a clinical interview, some self-report scales to aid in the assessment of the clinical picture, such as the Multidimensional Anxiety Scale for Children (MASC) and SCARED, have been presented in the literature [2].…”
Section: Introductionmentioning
confidence: 99%